Local Transmittance Measurements as Large Area Diagnostic Tool for the Optimization of Porous Si Foils for Li-Ion Battery Anodes. Issue 14 (1st January 2016) - Hansen, Sandra; Schütt, Andreas; Carstensen, Jürgen; Adelung, Rainer
Abstract : Silicon with its exceptionally high gravimetrical capacity of 4200 mAh/g has a great potential as anode material for Li-ion batteries. However, several critical problems have to be overcome to realize the up-scaling of the anodes from lab scale to mass production, especially with respect to long term cyclability and low cost fabrication techniques. In this paper, large area etched porous silicon foils are optically characterized with respect to local homogeneity in porosity and thickness and further prepared for a novel and promising type of anodes for Li-ion batteries. Since large areas (larger than 250 cm 2 ) have to be analyzed locally with high spatial resolution (smaller than 50 μm), a fast and contactless solar cell local characterization technique (CELLO [J. Carstensen, A. Schütt, G. Popkirov, and H. Föll, Phys. Status Solidi C 8(4), 1342 (2011)]) has been modified to measure the reflectance and transmittance of the porous silicon foils. The successful translation of the map data into local porosity and thickness informations of the porous silicon foils helps to modify the process parameters of the large area etching but more importantly allows a stable and cost effective new anode. This study illustrates the promising new battery concept based on a PorSi foil with adjustable porosities between 40 to 60 %.